Impact of simultaneous placement of implant and block bone graft substitute: an in vivo peri-implant defect model - Minh Khai Le Thieu (BMC, 2021)
Abstract Background Insufficient bone volume around an implant is a common obstacle when dental implant treatment is considered. Limited vertical or horizontal bone dimensions may lead to exposed implant threads following placement or a gap between the bone and implant. This is often addressed by bone augmentation procedures prior to or at the time of implant placement. This study evaluated bone healing when a synthetic TiO2 block scaffold was placed in circumferential peri-implant defects with buccal fenestrations. Methods The mandibular premolars were extracted and the alveolar bone left to heal for 4 weeks prior to implant placement in six minipigs. Two cylindrical defects were created in each hemi-mandible and were subsequent to implant placement allocated to treatment with either TiO2 scaffold or sham in a split mouth design. After 12 weeks of healing time, the samples were harvested. Microcomputed tomography (MicroCT) was used to investigate defect fill and integrity of the block scaffold. Distances from implant to bone in vertical and horizontal directions, percentage of bone to implant contact and defect fill were analysed by histology. Results MicroCT analysis demonstrated no differences between the groups for defect fill. Three of twelve scaffolds were partly fractured. At the buccal sites, histomorphometric analysis demonstrated higher bone fraction, higher percentage bone to implant contact and shorter distance from implant top to bone 0.5 mm lateral to implant surface in sham group as compared to the TiO2 group. Conclusions This study demonstrated less bone formation with the use of TiO2 scaffold block in combination with implant placement in cylindrical defects with buccal bone fenestrations, as compared to sham sites.